Analysis of the Influence of Health Information Systems and Work Motivation on Employee Performance through Job Satisfaction as a Mediation Variable - Fikdawati, Ria; Wardoyo, Dewie Tri Wijayati; Witjaksono, Andre Dwijanto (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2024)
This research aims to identify the influence of the health information system (SIK) and work motivation on employee satisfaction and performance at the Surabaya City Health Service Community Health Center, with job satisfaction as a mediating variable. This research uses a quantitative approach with a survey method. Data was collected through questionnaires distributed to 317 respondents selected using cluster techniques random sampling. Data analysis was carried out using a Structural Equation Model (SEM) based on Partial Least Square (PLS) to test the research hypothesis. The research results show that GIC has no effect on satisfaction. Work motivation was found to have a significant influence on job satisfaction. Motivated employees tend to have higher job satisfaction, driven by factors such as recognition, responsibility, and advancement opportunities. Apart from that, this research found that SIK did not have a significant effect on employee performance but work motivation had a positive effect on employee performance. Job satisfaction was also found to have a significant effect on employee performance, indicating that satisfied employees tend to have better performance. Job satisfaction is not proven to mediate the influence of SIK on employee performance, but it does mediate the influence of work motivation on employee performance. This research provides practical implications for Puskesmas management and policy makers in the health sector to focus on developing effective SIK and programs to increase work motivation to increase employee satisfaction and performance. The results of this research also provide theoretical contributions by enriching the literature on the influence of SIK and work motivation on individual performance in the context of health service organizations.